Effects of Three Resistance Exercise Orders on Muscular Function and Body Composition in Older Women - Dib, Márcia M.; Tomeleri, Crisieli M.; Nunes, João Pedro; Cunha, Paolo M.; Ribeiro, Alex S.; Schiavoni, Durcelina; Cavalcante, Edilaine F.; Kunevaliki, Gabriel; Teixeira, Denilson C.; de Oliveira, Arli R.; Gonçalves, Ezequiel M.; Gobbo, Luís A.; Silva, Analiza M.; Sardinha, Luís B.; Cyrino, Edilson S. (International Journal of Sports Medicine, 2020)
The purpose of the present study was to compare the effects of three resistance exercise orders on muscular strength, body composition, and functional fitness in trained older women. Forty-five women (aged ≥60 years), after performing 12 weeks of a pre-conditioning resistance-training program were randomly assigned in one of the following groups that performed the exercises in the following orders: multi-joint to single-joint order (MJ-SJ, n=15), single-joint to multi-joint order (SJ-MJ, n=15), and alternating between upper and lower body order (ALT, n=15). Specific training intervention lasted 12 weeks (3x/week) and was composed of eight exercises performed in three sets of 15/10/5 repetitions, with increasing load through the sets. Muscular strength was estimated by one-repetition maximum tests; body composition was assessed by whole-body dual-energy x-ray absorptiometry, and functional fitness was analyzed with a sequence of four motor tests. All groups improved similarly in muscular strength (Cohen’s effect size: MJ-SJ=0.45; SJ-MJ=0.48; ALT=0.45), skeletal muscle mass (MJ-SJ=0.08; SJ-MJ=0.07; ALT=0.09), and functional test performance (MJ-SJ=0.38; SJ-MJ=0.20; ALT=0.31), but no change was observed for body fat (P>0.05). The results suggest that 12 weeks of resistance training induce positive changes in muscle morphofunctionality, regardless of the exercise order employed in trained older women.
Keywords: aging; elderly; strength training; hypertrophy; autonomy; functional capacity